2016
DOI: 10.1371/journal.pone.0154492
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Cry1F Non-Recessive Resistance Alleles in North Carolina Field Populations of Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: Fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), is a target species of transgenic corn (Zea mays L.) that expresses single and pyramided Bacillus thuringiensis (Bt) toxin. In 2014, S. frugiperda were collected from a light trap in North Carolina, and a total of 212 F1/F2 isofemale lines of S. frugiperda were screened for resistance to Bt and non-Bt corn. All of the 212 isolines were susceptible to corn tissue expressing Cry1A.105 + Cry2Ab, Cry1F + Cry1A.105 + Cry2Ab, and Cry1F + Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 41 publications
(64 reference statements)
0
38
0
1
Order By: Relevance
“…In the same study, < 2% resistance allele frequencies were estimated for Florida and Texas S. frugiperda populations. Recently, studies in the US found resistance in S. frugiperda populations from North Carolina , …”
Section: Resultsmentioning
confidence: 99%
“…In the same study, < 2% resistance allele frequencies were estimated for Florida and Texas S. frugiperda populations. Recently, studies in the US found resistance in S. frugiperda populations from North Carolina , …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recent susceptibility surveys suggest resistance in different areas of Florida may be of independent evolutionary origin [46,47]. Resistance alleles were detected at low frequency in North Carolina, which receives annual migrants from Florida [48]. Population genetic and atmospheric trajectory analyses have effectively ruled out a Caribbean origin of the Cry1F resistance found in Brazil [49 ].…”
Section: Spread Of Resistance During Species Invasion or Range Expansionmentioning
confidence: 99%
“…Studies have shown that Cry1Ab and Cry1Ac are not highly effective for control of S. frugiperda . Additionally, S. frugiperda has already developed field resistance to Cry1F corn in Puerto Rico, Brazil, and the southeast region of the US mainland . Because of strong cross‐resistance among Cry1 proteins in Cry1F‐resistant S. frugiperda , none of the Cry1 proteins in the market is effective against S. frugiperda where Cry1F resistance is present.…”
Section: Introductionmentioning
confidence: 99%